2008
DOI: 10.1093/sleep/31.12.1683
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of In Utero Exposure to Smoking on Sleep Patterns in Preterm Neonates

Abstract: High prenatal smoking exposure modifies sleep patterns in preterm neonates by disrupting sleep organization and increasing nocturnal body movements. These findings raise the question of the repercussions of these sleep disturbances (at what is a critical stage in brain development) on the child's physiological and neurobehavioral outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 27 publications
2
20
1
1
Order By: Relevance
“…The finding that prenatal nicotine exposure predicted sleep problems in children is consistent with studies of smokers showing sleep disruption attributable to nicotine27, 28 and supports a recent study which found that prenatal maternal smoking resulted in less sleep and more fragmented sleep among newborns12. Preclinical studies of prenatal nicotine exposure have shown abnormal cardiorespiratory response during sleep29, altered sleep-state maturation30, and decreased Rapid Eye Movement (REM) sleep31.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The finding that prenatal nicotine exposure predicted sleep problems in children is consistent with studies of smokers showing sleep disruption attributable to nicotine27, 28 and supports a recent study which found that prenatal maternal smoking resulted in less sleep and more fragmented sleep among newborns12. Preclinical studies of prenatal nicotine exposure have shown abnormal cardiorespiratory response during sleep29, altered sleep-state maturation30, and decreased Rapid Eye Movement (REM) sleep31.…”
Section: Discussionsupporting
confidence: 85%
“…Sleep studies with prenatally exposed children have been limited almost entirely to infancy. Observable decrements in sleep duration and continuity and in sleep-state organization have been found in infants with prenatal cocaine exposure7-10 and, more recently, in infants with prenatal exposure to alcohol11 and nicotine11, 12. In addition, differences in electroencephalographic sleep patterns between exposed and unexposed infants have been demonstrated in studies of prenatal exposure to opiates13, alcohol14, and nicotine15.…”
mentioning
confidence: 96%
“…Previous studies have found an association of maternal prenatal smoking and smoking in early infancy with shorter sleep duration among infants. 11, 25 Our findings suggest that the observed association between smoking and sleep duration may be, in part, explained by parental sociodemographic characteristics.…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, smokers tend to experience a longer duration of light sleep than deep sleep compared to nonsmokers (Zhang, Samet, Caffo, Bankman, & Punjabi, 2008). These disturbances have also been observed in utero between fetal exposure by a mother's smoking (Stéphan-Blachard et al, 2008) and from secondhand smoke exposure (Ohida et al, 2007).…”
mentioning
confidence: 99%